Pre conception dyslipidemia and risk for preeclampsia in women undergoing IVF ET - Shaomin Chen; Yang Wang; Zhaoyu Wang; Liyuan Tao; Yongqing Wang; Yuan Wei; Zhaoping Li; Rong Li (Scientific Reports)
Abstract This study investigated the relationship between dyslipidemia prior to conception and the risk of preeclampsia (PE) in women pregnant by in vitro fertilization and embryo transfer (IVF-ET). The retrospective cohort study consisted of 2994 women who conceived by IVF-ET and delivered live neonates. The study population was divided into two components: a training set for the prediction model development (2288 women) and a test set for validation (706 women). Multivariable logistic regression was used for the development and validation of predictive model for the risk of PE. Among the 2288 women in the training set, 266 women (11.6%) developed PE. Multiple logistic regression analysis identified independent predictors for PE: triglyceride (TG) [adjusted odds ratio (aOR) 1.284; 95% confidence interval (CI) 1.113–1.489, P < 0.001]; pre-pregnancy BMI; pre- chronic hypertension; twin pregnancy; embryo transfer protocol. These independent predictors for PE were used to form a risk prediction model, and the area under the receiver-operator characteristic (ROC) curve (AUC) in the training and the test set was 0.77 (95% CI 0.73–0.80)and 0.71 AUC (95% CI 0.65–0.77), respectively. In conclusion, higher TG levels before pregnancy were independently associated with the risk for PE in women pregnant by IVF-ET.